(untitled) (Research, Society and Development, 2020)
Supernumerary teeth are anomalies in number development observed during routine dental examination. Mesiodens is the dental anomaly most frequently seen in permanent dentition, being considered the most common cause of incisor impaction, followed by odontomas and trauma. The most frequent location is in the anterior region of the maxilla and in most studies, it has a conical shape and a short root, which may be single or in pairs, erupted, included and inverted. The diagnosis and treatment depend on several factors such as: position, type and impaction of the supernumerary tooth next to the adjacent teeth. The present study aims to report the case of a patient, 7 years old, who attended the Dental Clinic of Centro Universitário Tiradentes reporting that the tooth was positioned incorrectly. After clinical and radiographic examination, the presence of a mesiodens found in the region of the left upper central incisor was found. It was also observed the delay in the eruption of the tooth mentioned, therefore, it was decided to perform the surgical removal of the supernumerary. About three weeks after the extraction, the permanent element started to erupt, proving the suspicion that it was being impacted by the supernumerary element. It was then possible to realize that the faster the diagnosis, the better the prognosis, since there may be several consequences such as resorption of the permanent tooth, formation of cysts, malocclusion, aesthetic compromise.